Determining the Areas Most Affected by Flood and Statistical-Synoptic Analysis of Flood Events In East Azerbaijan Province - Mehdi Eslahi; Farnaz Pourasghar; Younes Akbarzadeh; Mohammad Omidfar; Naser Mansouri Derakhshan; Abbas Shahmary (Nīvār)
In this Research, the most affected areas by flood of the province were identified using the flood damage information of regional water and crisis management for the period of 1999-2018, and a map of the spatial distribution and frequency of flood events was provided. The highest frequency of floods occurred in the western part of the province, especially in the cities of Marand, Shabestar and Tabriz, among which floods with a frequency of more than 10 days occurred in the cities of Tabriz, Shabestar, Marand, Jolfa and Sarab. In order to determine synoptic patterns for each day of torrential and heavy rainfall in the province, the upper levels map of the atmosphere, as well as indices of atmospheric instability along with the skew-T diagram were examined. The systems were classified based on the origin of the systems and 7 systems were identified, which include the high pressure of Siberia, the Black Sea, the Mediterranean and the Red Sea, as well as a combination of these systems. The highest number of systems is related to the Mediterranean system with 78 cases and the Mediterranean and Black Sea system with 54 cases in the second place. Precipitation systems are divided into two dynamic and thermal categories in terms of the air rising factor, and the frequency of systems leading to flooding is generally 58% related to dynamic systems and 42% of them related to thermal systems caused by the formation of local convective clouds.